Implementasi Model Pembelajaran Kooperatif Tipe Student Team Achievement Division Dalam Menguatkan Karakter Tanggung Jawab Peserta Didik Pada Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) MIN 4 Tulungagung - Venytia Eka Lukitasari; Luk-luk Nur Mufidah (The Elementary Journal, 2024)
This research is motivated by the character of responsibility which is an important character. According to the data that has been obtained, MIN 4 Tulungagung has implemented a cooperative approach, one of which is the (STAD) Model. With this model, the good character that emerges is the character of responsibility. The research focus in writing this thesis is how to plan, implement and evaluate the model (STAD). The aim of this research is to describe in depth the planning, implementation and evaluation of the learning model (STAD) to strengthen the character of responsibility. This research uses a qualitative descriptive research method. Data was obtained through interviews, observation and documentation. Data analysis uses data condensation, data presentation, and drawing conclusions. Test the validity of the data using a credibility test which includes increased persistence and triangulation. The results of this research show that the STAD model planning used includes activities for planning the learning process, preparing competent staff and teachers who already have a teacher certification certificate. For the implementation stage of the STAD or discussion model, the STAD steps are followed, namely: the teacher presents lessons, forms discussion groups, gives discussion group assignments and individual assignments, provides learning evaluations and awards, and finally the teacher and students draw conclusions about the learning. There are two stages of evaluating the STAD learning model, namely the teacher evaluates the students' abilities and evaluates the students' responsible character through the STAD model.